Comparative Study on Thermal Performance of Mud Rammed and Concrete Residential Building Envelope in Paro - Bhutan - Ugyen Wangchuk; Chorten TsheringTamang; Pema Rinzin; Samten Lhendup (International Journal of Energy and Thermal Applications, 2026)
A key factor in assessing the total energy efficiency of a building is the thermal performance of the building envelope. In Bhutan the building energy sector accounts for 15% of the total domestic electricity consumption out of which 50 to 60% accounts for space heating in the temperate region. Previous research findings and data also indicate that heat loss or gain through the building envelop were the most significant contributor accounting for 40 to 70% of the total heat losses.Bhutan is a country known for its traditional architecture, which makes extensive use of locally sourced natural materials. Mud rammed walls have been a defining feature of Bhutanese construction for centuries due to their durability, availability and excellent insulation properties. However, in recent years, there has been a notable shift towards concrete-based building envelope, which has raised concerns about their thermal energy performance and long-term sustainability.This study presents a comparative study on thermal performance of traditional and modern wall materials used in Bhutan. The modern materials considered are red bricks, cement-stabilized earth block (CSEB) and autoclaved aerated concrete (AAC), while mud walls represent traditional construction. A residential building in Paro, Bhutan has been used as model building. The model building was simulated in SketchUp with OpenStudio plugin software to evaluate and compare the thermal performances of these materials used in Building envelope. The simulation results obtained are analyzed, compared and discussed in the subsequent sections under results and discussions.
Keywords: Building; Comfort; cooling; demand; efficiency; energy; heating